Adjustment of norm-referenced and criterion-referenced evaluations of students’ knoweledge - Navickienė, Olga; Krylovas, Aleksandras (Lietuvos matematikos rinkinys, 2012)
Any evaluation of knowledge is performed in accordance with one of the two principles of evaluation – normative or criteria. An evaluation criterion is based on student’s knowledge (abilities, skills, competencies) comparison with certain standards usually described in a programme of a subject. Knowledge of students of almost all Lithuanian universities is evaluated in such principle. Another evaluation – normative – provides a comparison of outcomes with each other. For example, students are assessed in state examinations. Theoretical and practical aspects of normative evaluation and possibilities to apply them to assess students’ knowledge are discussed in this article.